A conceptual model for groundwater flow and geochemical evolution in the southern Outaouais Region, Québec, Canada. (July 2015) - Montcoudiol, N.; Molson, J.; Lemieux, J.-M.; Cloutier, V.
Highlights: Geochemical and isotope data help constrain the 2D conceptual flow model. Stable isotopes indicate recharge occurring under conditions similar to current climate. Mixing was found between younger ( 3 H) and older ( 14 C and 4 He) groundwater. Mixing occurred under natural flow conditions and/or was induced during sampling. The new conceptual model shows dominant local and intermediate flow systems. Abstract: A conceptual model was developed for a hydrogeological flow system in the southern Outaouais Region, Quebec, Canada, where the local population relies heavily on groundwater pumped from shallow overburden aquifers and from deeper fractured crystalline bedrock. The model is based on the interpretation of aqueous inorganic geochemical data from 14 wells along a cross-section following the general flow direction, of which 9 were also analysed for isotopes (δ 18 O, δ 2 H, 3 H, δ 13 C, 14 C) and 4 for noble gases (He, Ne, Ar, Xe, Kr). Three major water types were identified: (1) Ca–HCO3 in the unconfined aquifer as a result of silicate (Ca-feldspar) weathering, (2) Na–Cl as a remnant of the post-glacial Champlain Sea in stagnant confined zones of the aquifer, and (3) Na–HCO3, resulting from freshening of the confined aquifer due to Ca–Na cation exchange. Chemical data also allowed the identification of significant mixing zones. Isotope and noble gas data confirm the hypothesis of remnant water from the Champlain Sea and also support the hypothesis of mixing processes between a young tritium-rich component with an older component containing high 4 He concentrations. It is still unclear if the mixing occurs under natural flow conditions or if it is induced by pumping during the sampling, most wells being open boreholes in the bedrock. It is clear, however, that the hydrogeochemical system is dynamic and still evolving from induced changes since the last glaciation. As a next step, the conceptual model will serve as a basis for groundwater flow, mass transport and geochemical modelling to validate the hypotheses developed in this paper.